À mesa com escritores canibais: devoração e literatura - Ivana Teixeira Figueiredo Gund (2018)
Cannibalism a theme that permeates many areas of culture, times and spaces, and encloses, in different perspectives, historical scenes, mythologies and artistic languages is considered in this study in the quest for a similarity to the process of creation of a literary text. A researchbased on bibliographical studies and other forms of art dealing with the subject, such as the plastic and cinematographic arts, as well as theoretical contributions and literary works of Brazilian Literature and universal literature led to the finding that this theme moves throughtwo cultural tópos food and transgression. These concepts allowed the approach to the literary text through its cannibalistic facet and required further inquiries into possible meanings and categories of cannibal devouring. Limitations of time and space in the process of writing thisthesis led to restriction in the scope of research to Brazilian Literature and, within it, authors with a cannibal feature. It became apparent that in the work of some writers, theme transcended the mere pages of their writings and the fictional construction of their characters, becoming a political, conscious, reflective standpoint evidenced in their creative process. Through analytic categories, the re-making of the concepts of cannibal and cannibalism, revenge, enemy, ways of killing and eating, a metaphor of the cannibal-writer was constructed, Among the writers who present this characteristic, João Ubaldo Ribeiro and Antônio Torres were selected, due to their cannibalistic devouring approach to a corpus composed by official documents and formatter speeches of the Brazilian nation and its people. Since the devouring of a historical corpus was observed to be conscious in both authors, the creative processes have been here considered as literary kitchens, in which the transformation of the devoured corpse/body, as if in the molds of cooked food, becomes a singular expression of contemporary literature.